A disjointed multi-campus system: the neo-liberal expansion and fragmentation of Mozambican higher education. Issue 1 (2nd January 2017) - Langa, Patrício
Abstract : This paper tries to accomplish two tasks. First, it uses a critical review of the concept of differentiation to shed light on the expansion of the Mozambican higher education system, a consequence of the global neoliberal dynamics of higher education. Second, the neoliberal framework is applied to account for the development of multi-campus systems in the country. The paper argues that, on the one hand, the dispersion of multi-campuses resulted from an early stage of loosely regulated expansion and differentiation of higher education in the context of the liberalisation of higher education. On the other hand, the competition for students, in a market driven economy dominated by the existence of two main public institutions absorbing two-thirds of the students, prompted the establishment of satellite campuses by both private and public institutions, with serious and adverse implications for quality.